Use of stylar ribonucleases in almond breeding - Batlle I.; Romero M.A.; Vargas F.J.; Tanriver E.; Lakhal H. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
There is a correlation between the incompatibility (S) alleles and the stylar ribonucleases revealed electrophoretically. Cultivars, selections and seedlings are analysed for stylar ribonucleases using Non-Equilibrium pH Gradient Electrofocusing and staining for RNase activity which allows their genotyping. Crosses are planned with cultivars or selections of known S genotypes. Some crosses are semi-compatible, the two parents having one S allele in common and the self-compatible parent is used as the male parent. In a few cases, known Sf homozygous genotypes have been used. In both approaches only self-compatible seedlings are obtained. The inheritance of stylar ribonucleases in almond progenies and their correlation with self-compatibility has also been established. In addition, this technique is also used to assign S genotypes to seedlings and selections raised. The rapidity with which results can be obtained and the moderate cost of equipment and consumables has made possible its practical use in our breeding programme.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)